The Limits and Consequences of Population Policy: Evidence from China's Wan Xi Shao Campaign - Babiarz, Kimberly Singer; Ma, Paul; Miller, Grant; Song, Shige (The Review of Economics and Statistics, 2026)
Most of China's fertility decline predates the famous One Child Policy — and instead occurred under its predecessor, the Wan Xi Shao, or Later, Longer, Fewer (LLF) campaign. Studying LLF's contribution to fertility and sex selection behavior, we find that LLF i) reduced China's total fertility rate by 0.95 births per woman (explaining 30.6% of its fertility decline), ii) doubled the use of male-biased fertility stopping rules, and iii) promoted postnatal selection (implying 180,000 previously unrecognized missing girls, or 19% of the total during our study period). Considering Chinese population policy to be extreme in global experience, our paper demonstrates the limits of population policy — and its potential human costs.